2013
DOI: 10.4161/auto.25468
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial DNA copy number in the hippocampus and peripheral blood during opiate addiction is mediated by autophagy and can be salvaged by melatonin

Abstract: Drug addiction is a chronic brain disease that is a serious social problem and causes enormous financial burden. Because mitochondrial abnormalities have been associated with opiate addiction, we examined the effect of morphine on mtDNA levels in rat and mouse models of addiction and in cultured cells. We found that mtDNA copy number was significantly reduced in the hippocampus and peripheral blood of morphine-addicted rats and mice compared with control animals. Concordantly, decreased mtDNA copy number and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 50 publications
8
88
0
Order By: Relevance
“…Consistent with previous observations that melatonin can restore morphine-induced autophagy 45 and kainic acid-induced autophagy, 61 we found that melatonin inhibited MPTP-induced autophagy and cell death in vitro. This salvaging effect of melatonin was CDK5-dependent, and knockdown or overexpression of CDK5 abolished the protective effect of melatonin on MPTP-induced autophagy and cell death.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous observations that melatonin can restore morphine-induced autophagy 45 and kainic acid-induced autophagy, 61 we found that melatonin inhibited MPTP-induced autophagy and cell death in vitro. This salvaging effect of melatonin was CDK5-dependent, and knockdown or overexpression of CDK5 abolished the protective effect of melatonin on MPTP-induced autophagy and cell death.…”
Section: Discussionsupporting
confidence: 92%
“…Mouse cortical neurons were prepared and cultured using a previously described method. 45 Briefly, primary cortical neurons were isolated from mouse E15 embryos and were cultured in Neurobasal Ò Medium supplement with 2% B27 (Gibco-BRL, 17504).…”
Section: Reagents Chemicals and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B). The small increase in mtDNA accumulation is expected for the short time course, given ∼2× increases in mtDNA levels in models of prolonged and/or steady-state mitophagy deficiency/impairment (23). Collectively, these findings indicate that inflammasome activation leads to a Caspase-1-dependent block of mitophagy.…”
Section: Inflammasomes Mediate Parkin Cleavage and Inhibit Mitophagymentioning
confidence: 80%
“…Intracellular ROS production was evaluated using membrane-permeable probe DCFH-DA assay as described previously [34]. HUVECs were cultured in medium of normal glucose, high glucose and high glucose + FGF21 (30 nM) for 48 hours, and then washed with PBS followed by incubation in medium containing 20 µmol/L DCFH-DA at 37°C for 2 hours.…”
Section: Methodsmentioning
confidence: 99%